2014
DOI: 10.1111/pme.12327
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Quality and Usability of Smartphone Apps for Pain Self-Management

Abstract: Variation in app quality and a lack of user and clinician engagement in development were found across the pain apps in this research. Usability testing identified a range of user preferences. Although useful information was obtained, it would be beneficial to involve users earlier in the process of development, as well as establishing ways to merge end user requirements with evidence-based content, to provide high-quality and usable apps for self-management of pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
111
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(118 citation statements)
references
References 19 publications
3
111
0
4
Order By: Relevance
“…Die freie Verfügbarkeit von Apps im Gesundheitssektor ist jedoch als problematisch zu beschreiben, da die Bedürf-nisse der Nutzerinnen in der Regel außer Acht gelassen werden [17], die Evidenz in Bezug auf den Nutzen der App nicht ausreichend belegt ist [10], eine mangelnde Transparenz in Bezug auf den Schutz personenbezogener Daten vorliegt [7] und die Veröffentlichung von Apps meist Vorrang vor deren Qualität und Nutzen hat [14]. Die Anzahl der schmerzbezogenen Objectives.…”
Section: Hintergrund Und Fragestellungunclassified
“…Die freie Verfügbarkeit von Apps im Gesundheitssektor ist jedoch als problematisch zu beschreiben, da die Bedürf-nisse der Nutzerinnen in der Regel außer Acht gelassen werden [17], die Evidenz in Bezug auf den Nutzen der App nicht ausreichend belegt ist [10], eine mangelnde Transparenz in Bezug auf den Schutz personenbezogener Daten vorliegt [7] und die Veröffentlichung von Apps meist Vorrang vor deren Qualität und Nutzen hat [14]. Die Anzahl der schmerzbezogenen Objectives.…”
Section: Hintergrund Und Fragestellungunclassified
“…Determining and understating quality metrics of mobile applications industry is important to increase public awareness and competition for building high quality applications [11]. Metrics of TQM for mobile applicationsare a matter of debate but the benefits of implementation TQM methods are unlimited.…”
Section: Tqm Metrics For Mobile Applications and Cost Of Poor Qualitymentioning
confidence: 99%
“…Usability has a very important role in mobile applications.Some of usability mobile applicationsaspects are: ease of use, interface design, learnability, data entry methods, frequency of use, existing of shortcuts, familiar in vocabulary and flow of information [1]. Not all applications that need you to pay for to download are helpful or good quality [11]. Until recent years, mobile applications have been evaluated subjectively with no specific process.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…These systems are promising, but an authoritative review [12] found that these solutions do not suitably address the underlying psychological issues associated with CP. Moreover, further reviews on pain management apps unanimously identified that there is a lack of clinical engagement within the development cycle of systems and also state that efficacious claims are underpinned by little evidence [28,29]. Lastly, the majority of mobile health systems (mHealth) for chronic pain do not leverage the array of onboard sensors on smart-phones in order to provide passively acquired information [30,31].…”
Section: Mobile Apps For Chronic Pain Self-managementmentioning
confidence: 99%